Life Within a Contaminated Niche: Comparative Genomic Analyses of an Integrative Conjugative Element ICEnahCSV86 and Two Genomic Islands From Pseudomonas bharatica CSV86T Suggest Probable Role in Colonization and Adaptation - Mohapatra, Balaram; Malhotra, Harshit; Phale, Prashant S. (Frontiers in Microbiology, 2022)
Comparative genomic and functional analyses revealed the presence of three genomic islands (GIs, > 50Kb size): ICEnahCSV86, PBGI-1, and PBGI-2 in the preferentially aromatic-degrading soil bacterium, Pseudomonas bharatica CSV86T. Site-specific genomic integration at or near specific tRNAs, near-syntenic structural modules, and phylogenetic relatedness indicated their evolutionary lineage to the type-4 secretion system (T4SS) ICEclc family, thus predicting these elements to be ICEs. These GIs were found be present as a single copy in the genome and the encoded phenotypic traits were found to be stable, even in the absence of selection pressure. ICEnahCSV86 harbours naphthalene catabolic (nah-sal) cluster, while PBGI-1 harbours Co-Zn-Cd (czc) efflux genes as cargo modules, whereas PBGI-2 was attributed as a mixed function element. ICEnahCSV86 has been reported to be conjugatively transferred (frequency of 7x10-8/donor cell) to Stenotrophomonas maltophilia CSV89. Genome-wide comparative analyses of aromatic-degrading bacteria revealed nah-sal clusters from several Pseudomonas spp. as part of probable ICEs, syntenic to conjugatively transferable ICEnahCSV86 of strain CSV86T, suggesting it to be a prototypical element for naphthalene degradation. It was observed that the plasmids harbouring nah-sal clusters were phylogenetically incongruent with predicted ICEs, suggesting genetic divergence of naphthalene metabolic clusters in the Pseudomonas population. Gene synteny, divergence estimates, and codon-based Z-test indicated that ICEnahCSV86 is probably derived from PBGI-2, while multiple recombination events masked the ancestral lineage of PBGI-1. Diversifying selection pressure (dN-dS=2.27-4.31) imposed by aromatics and heavy metals implied the modular exchange-fusion of various cargo clusters through events like recombination, rearrangement, domain reshuffling and active site optimisation, thus allowing strain to evolve, adapt and maximize the metabolic efficiency in a contaminated niche. The promoters (Pnah and Psal) of naphthalene cargo modules (nah, sal) on ICEnahCSV86 were proved to be efficient for heterologous protein expression in E. coli. GI-based genomic plasticity expands the metabolic spectrum and versatility of CSV86T, rendering efficient adaptation to the contaminated niche. Such isolate(s) are of utmost importance for their application in bioremediation and are probable ideal host(s) for metabolic engineering.